Innovation in informal settings but in which direction? The case of small cotton farming systems in Argentina - Arza, Valeria (2014)
We compare two very different kinds of innovation in the same informal setting; that of small-scale cotton production in northeast Argentina. One involved the informal production and sale of copied genetically modified seeds, an innovation that fitted readily within an incumbent set of socio-technical practices concerned with intensive commodity crop production. The other involved new agro-ecological techniques; a radical departure from incumbent practices. By contrasting these cases, we argue that the potential of informal innovation to better address the problems of marginalized actors depends on the broader socio-technical system to which innovation seeks to contribute.